CAREGIVERS PEMBELAJARAN MEMBACA BERBASIS AUDIO VIDEO PADA SISWA SDLB - Alexander Dharmawan; Ana Wahyuni; Alice Zellawati (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
he children have rights in getting education, as well as in Children with Special Needs (ABK). Children with Special Needs have one of the characteristics of having difficulty in the education process, so they need special services according to their form and degree of difficulty, such as in children of mental retardation. Based on preliminary research, it is known that from 7 SLB in Semarang there are 22 students class 1 until 5 which is mental retardation (MR) not fluent reading. The largest number of students who can not read is in SLB Widya Bhakti and SLB Swadaya as partner in this devotional. So it is necessary to do devotional activities, especially caregiver learning reading. This devotion aims to optimize the ability to read children mental retardation through learning to read audio-based video learning media with caregivers mentoring (parents and teachers). The methods used are seminar method, training of teaching materials and caregiversassistance to optimize reading ability in children mental retardation. Caregivers participation is actively expected to create an interactive learning atmosphere and fun for the children because the assistance is done both at school and at home, so that the learning outcomes become more optimal. The results of this activitystudents can read fluently in a short time with video-based learning model of video.Keywords : Mental Retardation, Children with Special Needs, Caregivers, Audio Video.